Coralline-like CoP3@Cu as an efficient electrocatalyst for the hydrogen evolution reaction in acidic and alkaline solutions. (23rd October 2020) - Hou, Mengyu; Xu, Ying; Li, Xi; Dong, Yongzhi; Sun, Fengke; Tang, Dan; Cai, Minkun; Jin, Chenglong; Dong, Yulin; Qu, Deyu; Xie, Zhizhong; Lin, Yawei; et al.
Abstract : CoP3 @Cu/Cu exhibited excellent catalytic activity and stability in acidic and alkaline media. Abstract : The synthesis of low-cost and efficient electrocatalysts for the hydrogen evolution reaction (HER) is highly challenging. And apart from the intrinsic activity, the structure of the electrocatalysts also plays a vital role in the highly efficient catalysis for the hydrogen evolution reaction. Herein, the H2 bubbling-assisted electroplating method was employed to construct a coralline-like structure of Cu on the copper plate. And then, cobalt phosphide (CoP3 ) was successfully electrodeposited on the structure to form a CoP3 @Cu/Cu electrode. Benefitting from this unique structure, the optimized CoP3 @Cu/Cu exhibited an excellent electrocatalytic activity for the HER with Tafel slopes of 44 and 82 mV dec −1 in 0.5 M H2 SO4 and 1 M KOH electrolytes, respectively. To reach a current density of 10 mA cm −2, an overpotential of 101 and 92 mV was required for the HER under acidic and alkaline conditions, respectively. Moreover, the CoP3 @Cu/Cu electrode exhibited a long-term stability for the HER, indicating a promising prospect in the application.